Implementation of Diversion against Criminal Conduct of Narcotics Conducted by Children - Heru Pramu Apriliyanto; Achmad Sulchan (Law Development Journal, 2021)
The aim of this research is To know and analyze application of diversion to offenders of narcotics crimes committed by children in law enforcement construction at the Cirebon City Police Drug Research Unit. To find out and analyze what factors are the obstacles application of diversion to offenders of narcotics crimes committed by children in law enforcement construction at the Cirebon City Police Drug Research Unit and the solution. This study uses an empirical juridical approach, with descriptive analytical research specifications. The data used in this study are secondary data obtained through library research and primary data obtained through field research interviews with investigators at the Cirebon City Police Drug Research Unit. The results of this study are Application of Diversion Against Perpetrators of Narcotics Offenses Committed by Children in Law Enforcement ConstructionIn the Drug Research Unit of the Cirebon City Police, namely: a) Diversion is carried out by the investigator with the perpetrator/victim and/or his family, community counselors, and involving community leaders. Diversion is carried out by deliberation or mediation which results in a diversion agreement. b) After the Investigator issues the Investigation Termination Order, the Minutes, Diversion Agreement and the Decision of the Head of the District Court are copied to the Public Prosecutor as the basis for the Public Prosecutor to return the SPDP, so that the case becomes inkracht.Barriers: a) Legal Substance Factors b) Legal culture factors c) Community Factors d) Law Enforcement Factors e) RPK Facilities and Infrastructure Factors. Solutions: a) Develop a work plan and maximize the performance of each investigator in handling child cases. b) Establishing Intensive Communication with other Law Enforcement Officials. c) Holding Diversion Socialization among the Community d) Making an Agreement on Supervision of the Implementation of the Diversion Agreement Results. e) Optimizing facilities and infrastructure.